Uptake of fIPV3 and implementation challenges as perceived by auxiliary nurse midwives at two primary healthcare centers in urban Bengaluru: a mixed-method study - Krishnappa, Kashvi Bijavara; Nagaraja, Sharath Burugina; M. D., Sangeetha; Menon P. K., Sreenath (International Journal Of Community Medicine And Public Health, 2024)
Background: India introduced fractional-dose inactivated poliovirus vaccine (fIPV) into its routine immunization program as part of the polio eradication and endgame strategic plan. The study aimed to assess the uptake of the 3rd dose of fIPV among eligible beneficiaries and explore the implementation challenges perceived by auxiliary nurse midwives (ANMs) at two primary healthcare centers in urban Bengaluru. Methods: A mixed-method study was conducted between April and May 2023. A cross-sectional design was used for quantitative objectives, while in-depth interviews were conducted with ANMs for qualitative insights. Data were collected through vaccination registers, questionnaires, and key informant interviews. The study population included all eligible beneficiaries for the 3rd dose of fIPV from January to March 2023. Results: Out of 296 eligible beneficiaries, 139 (47%) had received the 3rd dose of fIPV. The challenges faced by ANMs in fIPV3 implementation included difficulties in recording and reporting activities, fear of managing adverse events, lack of confidence in administering intradermal injections, obtaining consent from parents, inadequate training, and concerns about vaccine wastage and increased workload. Conclusions: The uptake of fIPV3 was suboptimal, and ANMs encountered several challenges during implementation. To enhance fIPV3 integration into the vaccination schedule, the health system needs to improve awareness among the community, strengthen health worker capacity, and provide better training and support. Strengthening routine immunization programs can contribute to sustained polio eradication efforts.